Бюджетна політика підтримки фінансової безпеки та стійкості фінансів домогосподарств регіонів України - Лисяк, Любов Валентинівна; Lysiak, Liubov; Качула, Світлана Валентинівна; Kachula, Svitlana (Дніпровський державний аграрно-економічний університет, ТОВ `ДКС Центр`, 2023)
У статті здійснено визначення особливостей та оцінка перспектив реалізації інструментарію бюджетної політики у підтримці фінансової стійкості та безпеки домогосподарств регіонів України в умовах воєнного стану. Вагомими чинниками, які останніми роками суттєво впливають на якісний рівень функціонування домогосподарств регіонів України є загострення економічних та, зокрема, фінансових ризиків, зумовлених не лише станом економіки, але першочергово - умовами й обставинами воєнного стану. Загострення фінансових ризиків суттєво впливає на погіршення фінансової стабільності домогосподарств і посилює навантаження на державний та місцеві бюджети. У роботі видокремлено ряд загальних факторів/умов, за яких фінансова стійкість домогосподарств буде стабілізуватися або підвищуватися, а ризикї ї погіршення - мінімізуватися. Відповідно оцінка і врахування потенційно можливих та реально існуючих фінансових ризиків, що впливають на фінансову стійкість домогосподарств, є важливою вимогою сучасності при розробці і реалізації обґрунтованої бюджетної політики як держави, так і адміністративно-територіальних утворень. При цьому важливого значення набуває врахування та коригування процессу формування відповідного інституційного середовища у дотриманні вимог фінансової безпеки, як вагомої складової фінансово-економічної безпеки країни загалом, та стійкості фінансів домогосподарств. The article identifies the specifics and evaluates the prospects for the implementation of the budget policy tools in maintaining the financial stability and security of the finances of households in certain regions of Ukraine in the conditions of martial law. Important factors affecting the quality level of functioning of households in the regions of Ukraine are economic and, in particular, financial risks caused not only by the state of the economy, but primarily by the conditions and circumstances of martial law. The aggravation of such risks significantly worsens the financial condition of households and increases the burden on state and local budgets. Accordingly, the assessment and consideration of financial risks is an important modern requirement and needs to be taken into account when developing a sound budget policy of both the state and administrative-territorial units. The state and development of the institutional environment (institutional conditions) is of great importance in meeting the requirements of financial security, as an important component of the country's financial and economic security in general, and the stability of household finances in particular. It was concluded that an effective/resulting budget policy operates with a significant number of tools and levers that, under the conditions of timely and effective use, can provide significant support to households in difficult life conditions, as well as become a starting point, an impetus for the progressive safe development of territories, communities, households and countries. The latter is possible with effective decision-making regarding budget policy priorities, the adaptability of its tools to the challenges of wartime and post-war economic recovery and the need for the development and involvement of human capital in the national economy, compliance with financial security requirements. It is important to overcome certain inertia, increase the efficiency of budget policy, more actively use its tools to support the livelihood of households in war conditions, apply simplified social support mechanisms to internally displaced households, as well as households that have lost property or other means of normal life as a result of the war and other household members who have a legally established right to do so.
Budget policy of supporting financial security and financial stability of households in the regions of Ukraine
Keywords: домогосподарство; household; фінанси домогосподарств; household finances; фінансова стійкість домогосподарств; financial stability of households; бюджетна політика; budget policy; державний бюджет; state budget; місцеві бюджети; local budgets; видатки бюджету; budget expenditures; фінансовий ризик; financial risk; територіальна громада; territorial community; умови воєнного стану; martial law conditions; інституційне середовище; institutional environment